Efektivitas Bimbingan Kelompok dengan Problem Solving untuk Meningkatkan Motivasi dan Disiplin Belajar Siswa Tahfidz - Marpaung, Al Hudani; Daulay, Nurussakinah; Arsini, Yenti (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2025)
This study aims to examine the effectiveness of group guidance services with problem solving techniques in increasing the motivation and learning discipline of tahfidz students in a madrasah environment. This study used a quantitative approach with a quasi-experimental design, involving 20 purposively selected students from MTs Al-Washliyah Lubuk Amat, North Sumatra. Participants were divided into two groups: experimental and control. The experimental group attended six 60-minute structured group guidance sessions designed to foster self-awareness, identify learning barriers and formulate solutions independently. The intervention was designed by integrating the spiritual values and commitment that characterize tahfidz education. Data were collected through pre-test and post-test using a Likert scale questionnaire that has been tested for validity and reliability (r = 0.456-0.986; α = 0.871). The paired sample t-test results showed a statistically significant increase in scores in the experimental group (mean difference = 24.95; p = 0.000), with a very large effect size (Cohen's d = 2.51). These findings prove that problem-solving-based group guidance is effective in supporting the behavioral and cognitive development of students who face academic and spiritual demands simultaneously. Theoretically, this study integrates Bandura's self-efficacy theory with the Islamic counseling framework. Practically, this study presents an intervention model that can be replicated in educational institutions that organize tahfidz programs. This study fills a void in the literature related to structured psychopedagogical interventions in the context of religious value-based education.